Screening Disability Insurance Applications - Philip de Jong; Maarten Lindeboom; Bas van der Klaauw (Tinbergen Institute, 2006)
This paper investigates the effects of intensified screening of disability insurance benefit applications. A large-scale experiment was setup where in 2 of the 26 Dutch regions case workers of the disability insurance administration were instructed to screen applications more intense. The empirical results show that intense screening reduces long-term sickness absenteeism and disability insurance applications. This provides evidence both for direct effects of the more intensive screening on work resumption during sickness absenteeism and for self-screening by potential disability insurance applicants. We do not find any spillover effects to the inflow into unemployment insurance. A cost-benefit analysis shows that the costs of the intensified screening are only a small fraction of its benefits.
Keywords: J28; J65; 330; disability insurance; sickness absenteeism; policy evaluation; self-screening; experiment; Behindertenpolitik; Behinderte Arbeitskräfte; Versicherung; Fehlzeit; Kontrolle; Kosten-Nutzen-Analyse; Niederlande